Promising Hevea clones for Ribeira river valley region, Sao Paulo State, Brazil - Souza Goncalves P De; Furtado E L; Saes L A; Sakai M; Sambugaro R (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this paper was to show first selection results of IAC 300 and Amazonian IAN and FX series of rubber tree (Hevea brasiliensis) clones in a small scale trial evaluation, for yield, growth and SALB (South American leaf blight caused by Microcyclus ulei) performance. Yield and vigour of 20 clones were assessed for two and nine years, respectively, in Vale do Ribeira, SP, Brazil. In the IAC 300 series, four clones (IAC 301, IAC 304, IAC 306 and IAC 319) were classified as satisfactory for yield. The Amazonian clones IAN 6323, Fx 3864 and IAN 2903 produced 1078 kg, 945 kg and 900 kg/ha/year, respectively, higher than the control IAN 873 (878 kg/ha/year). All selected clones had vigorous growth, with the girth at opening (cm) ranging from 37.40 (IAN 4493) to 53.75 (IAN 6323) and tappability ranging from 7.0;(IAN 4493) to 100;(IAC 6323 and IAC 302), except for FX 3899 and IAN 3044. The IAC 315, with 7.37 mm, had greater thickness virgin bark than IAN 873 (6.44 mm). Concerning SALB performance, clones IAC 306, IAC 315, IAC 320 were the best for resistance.
Source Year: 2001
Keywords: Hevea brasiliensis; Hevea clones